The queer coat: Konstantin Goncharov's fashion, Russian masculinity and queer world building. Issue 1 (1st September 2019) - Strukov, Vlad
I re-assess Russian sartorial economics of the 1990s by examining fashion by Konstantin Goncharov, who was credited for styling Russian rock stars and making costumes for artistic projects. I focus on the relationship between queer masculinity and sartorial practice. The former relies on a visual code encompassing a range of multi-platform, cross-media strategies and a network of references. The latter refers to a community of individuals engaged in the production of a characteristic style across different sites. The article proposes the concept of queer world-building, which brings together object-oriented and community-oriented practices. Central to Goncharov's world is 'the queer coat', a costume designed for his clientele and a historically grounded metaphor for Russian society. It designates the process of creative re-modelling of pre-Soviet and Soviet aesthetics, producing a complex cultural exchange challenging dominant notions of masculinity. Goncharov's cross-platform and intermedial work captures the spirit of multi-centric cultural activity of the 1990s.